Defining a GP consultation - Lugg-Widger, Fiona; Jones, Hywel; Angel, Lianna; Cannings-John, Rebecca; Lau, Mandy; Hughes, Kathryn (International Journal of Population Data Science, 2018)
Introduction The method used to define a GP-consultation using routine data will vary depending on the data source and research question. However, without consensus the approach will be tackled by numerous researchers and invariably result in different definitions. The LUCI study is assessing outcomes of childhood UTI using routine data sources. Objectives and Approach We are interested in GP urine sampling rate and re-consultation rate. The GP dataset includes multiple clinical (acute, routine monitoring, prescribing, results) and administrative codes. A GP consultation therefore needed to be defined. GP read code frequencies for our study cohort of children were produced. One researcher reviewed the codes that represented 80% of the data and classified them as a consultation or not. Where there was uncertainty this was independently reviewed by two clinicians and discrepancies agreed by the management team. Results We will present the decisions and assumptions made for this study in defining a GP consultation. 25,623 Read Codes represented the consultations for our study cohort of which 460 codes represented 80% of the consultations. The remaining 20% of codes represented <0.032% of records each. The 460 Read Codes were reviewed and following independent review and agreement from the management group 149 Read Codes were excluded. These were grouped into the following categories Administrative (e.g. Incoming Mail Processing, Ethnicity codes), Vaccinations, Child Health (e.g. First Smiled), Asthma and Medication Review. The GP consultations to be included in the analysis were then restricted to exclude these codes. This has been an important step in cleaning and understanding the data prior to analysis. Conclusion/Implications A consultation was defined for this study however there will be pros and cons to this method. In lieu of a consensus approach to the method this work is the first step to sharing approaches to help researchers with the same challenge.